Implementasi QR Code Pada Perpustakan Dengan Metode RAD - Riyandi, Fikri Tara; Utomo, Hafidz Tri; Syabana, Hardi (Journal of Digital Literacy and Volunteering, 2023)
The library is a source of knowledge because that is where books are useful for those who need them. But today's libraries still use the old method of borrowing and returning books by library visitors, so visitors still find it difficult to borrow and return library books. Therefore we want to carry out a new innovation, namely by using QR Code technology to borrow and return books at the library which can make it easier for library visitors.